Coadministration of Compound Danshen dripping pills and bezafibrate has a protective effect against diabetic retinopathy - Liu, Le; Li, Xiaoqiang; Cai, Wenbin; Guo, Kaimin; Shi, Xuelian; Tan, Lu; Zhan, Yao; Jing, Xueshuang; Wang, Wenjia; Zhou, Shuiping; Sun, He; Zhang, Xu; et al. (Frontiers in Pharmacology, 2022)
Diabetic retinopathy (DR) is increasingly becoming a main complication of diabetes, and is difficult to cure. In our research, network pharmacology analysis suggested that both compound Danshen dripping pills (CDDP) and bezafibrate (BZF) have potential protective effects against DR and the two drugs may act synergistically. The pharmacological effects of the coadministration of CDDP and BZF were elucidated in db/db mice, which simulate DR. Fluorescein fundus angiography showed that coadministration attenuated vascular leakage. Optical coherence tomography and hematoxylin and eosin staining showed that coadministration improved retinal thickness better than CDDP monotherapy. In addition, cell fluorescence images of reactive oxygen species revealed that coadministration of CDDP and BZF had more potent effects against oxidative stress than CDDP monotherapy. Metabolomics analysis showed that coadministration reduced the ratio of oxidized glutathione to reduced glutathione further than CDDP monotherapy. Coadministration of CDDP and BZF may provide additional protective effects by resisting vascular leakage, increasing retinal thickness, and inhibiting inflammation and oxidative stress in DR.